The End-State Comfort Effect in 3- to 8-Year-Old Children in Two Object Manipulation Tasks - Knudsen, Birgit; Henning, Anne; Wunsch, Kathrin; Weigelt, Matthias; Aschersleben, Gisa (Frontiers in Psychology, 2012)
The aim of the study was to compare 3- to 8-year-old children’s propensity to anticipate a comfortable hand posture at the end of a grasping movement (end-state comfort effect) between two different object manipulation tasks, the bar-transport task, and the overturned-glass task. In the bar-transport task, participants were asked to insert a vertically positioned bar into a small opening of a box. In the overturned-glass task, participants were asked to put an overturned-glass right-side-up on a coaster. Half of the participants experienced action effects (lights) as a consequence of their movements (AE groups), while the other half of the participants did not (No-AE groups). While there was no difference between the AE and No-AE groups, end-state comfort performance differed across age as well as between tasks. Results revealed a significant increase in end-state comfort performance in the bar-transport task from 13% in the 3-year-olds to 94% in the 8-year-olds. Interestingly, the number of children grasping the bar according to end-state comfort doubled from 3 to 4 years and from 4 to 5 years of age. In the overturned-glass task an increase in end-state comfort performance from already 63% in the 3-year-olds to 100% in the 8-year-olds was significant as well. When comparing end-state comfort performance across tasks, results showed that 3- and 4-year-old children were better at manipulating the glass as compared to manipulating the bar, most probably, because children are more familiar with manipulating glasses. Together, these results suggest that preschool years are an important period for the development of motor planning in which the familiarity with the object involved in the task plays a significant role in children’s ability to plan their movements according to end-state comfort.